Nejen sociální aspekt plíživých společenských proměn - Brychtová, Šárka (Univerzita Pardubice, 2013)
The submitted article is going to potential changes of society in the near future. There are changes above all economic and social sphere in our society. The article, in its initiatives passages and chapters sketches potential causes of all-society changes that it perceives to a great extent in unlimited application of neoliberal access, that intensify in Europe in last 20-25 year, and that lead doubtless to restraint the role of state and to great asymmetry of public and private sector. The article, though try to return also another ambitions – and in not only in social, but also in philosophical and etic context refers to deeper causes of present and so many discussed and unsolvable imbalance.
Not only social aspects of slinking changes of our society
Keywords: economic crisis; globalization; public sector; concentration of power; transformation of thinking and society; causes of crisis; way from crisis; balance